PENYULUHAN PROGRAM BACK EXERCISES GUNA MENGATASI KELUHAN NYERI PUNGGUNG BAWAH PADA IBU PKK DESA KLEWOR BOYOLALI - Isti Nabila Nur Afifah; Arif Pristianto (LPPM Universitas Abdurrab, 2022)
Entering menopause, women will experience musculoskeletal disorders such as joint pain. One of the most common musculoskeletal complaints is low back pain. Low back pain is a musculoskeletal disorder characterized by pain, muscle tension, and muscle stiffness. Back pain localized between the costal margin and the inferior gluteal fold with or without pain radiating to the leg. Chronic low back pain can cause disability and reduce functional ability. One of the exercises to reduce complaints of low back pain is back exercise in the form of strengthening and stretching movements. This program is effective for improving physical abilities in the back and waist and reducing pain complaints. The method used in this activity is counseling and education about low back pain and the role of physiotherapy in dealing with low back pain. The result of this outreach activity was an increase in participants' knowledge which was evaluated using a pretest and posttest questionnaire. In addition, participants can also do the exercises that have been taught themselves to deal with complaints and educate others